Certain aspects of interaction between the state and civil law in CIS countries - Цуркан-Сайфуліна, Юлія Василівна; Цуркан-Сайфуліна, Ю. В.; Цуркан-Сайфулина, Юлия Васильевна; Tsurkan-Saifulina, Yuliia V.; Вітман, Костянтин Миколайович; Вітман, К. М.; Витман, Константин Николаевич; Vitman, Kostiantyn M.; Колодін, Денис Олексійович; Колодін, Д. О.; Колодин, Денис Алексеевич; Kolodin, Denys O. (Rushing Water Publishers Ltd., 2019)
Today, globalization processes are increasingly entering people’s lives and condition the continuous development of society as a fundamental principle of modern progress. Globalization, as an association based on global guidelines and the introduction of advanced technologies, is one of the main factors influencing the change in understanding of the essence of the state and civil law, their interconnection and interdependence. In the framework of the article, the author has analysed the influence of the state policy of the CIS countries on the national civil law of the studied states; features of state law-making and formal certainty, the general obligation of national civil law in the CIS countries have been revealed; the influence of the state on the implementation of civil law has been determined, and vectors for reforming national civil law in the CIS countries have been established in the context of its interaction with the state. As a result of the study, it has been established that the state has the opportunity not only to interact with civil law, but also to actively influence its content, and to protect the right from violations; the characteristic features of the influence of the political course on the national civil law of the CIS countries have been determined; it has been stated that the most significant influence of the state on civil law is made directly in the field of law-making and law enforcement; the author’s definition of the concept “model law-making in the field of civil law in the CIS” has been proposed; it has been argued that it is very advisable to build a scientifically sound, effective and comprehensive legal policy of the CIS member states.

Сьогодні процеси глобалізації все більше входять у життя людей і зумовлюють безперервний розвиток суспільства як фундаментальний принцип сучасного прогресу. Глобалізація, як об’єднання на основі глобальних орієнтирів та впровадження передових технологій, є одним із головних факторів, що впливають на зміну розуміння сутності держави та цивільного права, їх взаємозв’язку та взаємозалежності. У рамках статті проаналізовано вплив державної політики країн СНД на національне цивільне право досліджуваних держав; виявлено особливості державної правотворчості та формальної визначеності, загальної обов’язковості національного цивільного права в країнах СНД; визначено вплив держави на реалізацію цивільного законодавства, визначено вектори реформування національного цивільного законодавства країн СНД у контексті його взаємодії з державою. У результаті дослідження встановлено, що держава має можливість не лише взаємодіяти з цивільним законодавством, а й активно впливати на його зміст, захищати право від порушень; визначено характерні особливості впливу політичного курсу на національне цивільне право країн СНД; зазначено, що найбільш істотний вплив держави на цивільне право здійснюється безпосередньо у сфері правотворчості та правозастосування; запропоновано авторське визначення поняття «модельне правотворчість у сфері цивільного права СНД»; стверджується, що дуже доцільно будувати науково обґрунтовану, ефективну та комплексну правову політику держав-учасниць СНД.
Tsurkan-Saifulina Y. V. Certain aspects of interaction between the state and civil law in CIS countries / Y. V. Tsurkan-Saifulina, K. M. Vitman, D. A. Kolodin // Asia Life Sciences. - Supplement 21(2). - Rushing Water Publishers Ltd., 2019. - Р. 697-717.
Keywords: CIS; civil law; globalization; model law-making; rule of law; state; СНД; цивільне право; глобалізація; модельне правотворення; верховенство права; держава; Research Subject Categories::LAW/JURISPRUDENCE